A Correlation between Iodoplumbate and Photovoltaic Performance of Perovskite Solar Cells Observed by Precursor Solution Aging. Issue 5 (31st July 2019) - Shin, Gwang Su; Kim, Seul‐Gi; Zhang, Yong; Park, Nam‐Gyu
Abstract: This study reports the aging effect of a perovskite precursor solution on the photovoltaic performance of perovskite solar cells. The precursor solution is aged at different temperatures of 4, 25 (room temperature), and 65 °C. Power conversion efficiency (PCE) is found to depend on the aging condition. Average PCE increases with aging time, where optimal aging time for best the PCE decreases with aging temperature. Average PCE of 17.29% obtained from a 24 h aged solution at 4 °C is higher than that of 16.48% from a nonaged fresh solution. At 25 °C, a 2–4 h aged solution yields highest PCE of 17.41%. The aging effect is more accelerated at 65 °C, where the best PCE of around 17.10% is achieved from the solution aged for 1.5–2 h. It is commonly observed that photocurrent density is substantially influenced by aging time, while voltage is less affected. Fill factor declines with aging time regardless of aging temperature. Iodoplumbate PbI2 S4 (S = solvent) formed in the precursor solution increases its concentration, as aging time increases at a given temperature, which is beneficial for improving photovoltaic performance. No aging effect is found for excess MAI or PbI2 due to initially formed sufficient iodoplumbate. Abstract : Power conversion efficiency of the MAPbI3 ‐based perovskite solar cell is found to depend on the precursor solution aging, which is related to the iodoplumbate concentration formed in the precursor solution. Aging effect is solved by excess PbI2 in the MAPbI3 solution or addition of CsI in the FAPbI3 solution due to sufficient iodoplumabate formed initially.